2021
DOI: 10.3390/cells10113022
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Mitochondrial Homeostasis: The Role of PINK1 in Parkinson’s Disease

Abstract: The progressive reduction of the dopaminergic neurons of the substantia nigra is the fundamental process underlying Parkinson’s disease (PD), while the mechanism of susceptibility of this specific neuronal population is largely unclear. Disturbances in mitochondrial function have been recognized as one of the main pathways in sporadic PD since the finding of respiratory chain impairment in animal models of PD. Studies on genetic forms of PD have provided new insight on the role of mitochondrial bioenergetics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 150 publications
(201 reference statements)
0
30
0
Order By: Relevance
“…Although α-syn induces the response of various cells in CNS, recent studies also suggest that microglia and astrocytes play a minor role in the development of PD (Vizziello et al, 2021), the neurons themselves are more related to PD. The microglia and astrocytes play the role in regulating the neuroinflammatory response induced by α-syn.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although α-syn induces the response of various cells in CNS, recent studies also suggest that microglia and astrocytes play a minor role in the development of PD (Vizziello et al, 2021), the neurons themselves are more related to PD. The microglia and astrocytes play the role in regulating the neuroinflammatory response induced by α-syn.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The progression in oligodendrocytes has been detected in multiple system atrophy (MSA), a rare and atypical PD (Tu et al, 2021). An analysis sequence of about 17,000 nuclei from matched SN samples found that dopaminergic neuronspecific gene expression makes up the crucial genetic risk for PD, such as protein folding and ubiquitination pathways, mitochondrial functioning, and a distinct cell type associated with PD and oligodendrocyte-specific gene expression (Vizziello et al, 2021).…”
Section: Oligodendrocytes and Pdmentioning
confidence: 99%
“…The atypical features are dystonia, sleep benefit, and hyperreflexia [ 47 ]. Similar to PRKN, PINK1 contributes to the maintenance of mitochondrial homeostasis and regulates UPS function [ 21 , 243 ]. PINK1 mutations induce a complete loss of kinase activity, mitochondrial dysfunction, oxidative stress, impaired cellular metabolism, abnormal mitophagy, and altered proteostasis [ 21 , 47 ].…”
Section: Autosomal Recessive Genesmentioning
confidence: 99%
“…Interestingly enough, the great majority of these mutations appear to affect the nervous system. For example, mutations in PINK1 and Parkin are associated with early-onset forms of Parkinson’s Disease (PD) ( Borsche et al, 2021 ; Vizziello et al, 2021 ) while mutations in MFN2 are associated with axonal forms of Charcot-Marie-Tooth disease 2 (CMT2) and hereditary motor and sensory neuropathies (HMSN) ( Zaman and Shutt, 2022 ). Finally, mutations in OPTN have been linked to primary forms of glaucoma ( Sears et al, 2019 ) as well as amyotrophic lateral sclerosis (ALS) ( Benson et al, 2021 ).…”
Section: Mitophagy and Neurodegenerative Diseasesmentioning
confidence: 99%